The Carter administration’s policy towards Afghanistan - Xin Yin («Քոփի Փրինթ» տպագրատուն)
The Carter administration came to power at a crucial period when the relations between the East and the West were shifting from relaxation to re-confrontation. Its policy towards Afghanistan was not only restricted by the situation of U.S.-Soviet Union relations but also exerted a direct influence on the maintenance and transformation of this situation, notably the opening of the “New Cold War” between the East and the West. With the evolution of the Carter administration’s policy towards Afghanistan as the main clue, this paper aims to study the formation background, causes of change and development logic of different US policies towards Afghanistan in this period so as to reveal the internal relationship between the change of the U.S. policy towards Afghanistan and the evolution of the Cold War situation, as well as the essence of the U.S. policy. Քարթերի վարչակազմ, Խորհրդային Միություն, Աֆղանստան, նոր աշխարհակարգի ռազմավարություն, Քարթերի դոկտրինա, «նոր սառը պատերազմ», զարգացում: Քարթերի վարչակազմը իշխանության եկավ վճռորոշ ժամանակաշրջանում, երբ Արևելքի և Արևմուտքի հարաբերությունները հանգիստ վիճակից անցում էին կատարում նոր առճակատման։ Աֆղանստանի նկատմամբ նրա քաղաքականությունը ոչ միայն սահմանափակված էր ԱՄՆ-Խորհրդային Միություն հարաբերությունների ընթացքով, այլև անմիջական ազդեցություն է ունեցել դրա փոխակերպման վրա՝ մասնավորապես Արևելքի և Արևմուտքի միջև «նոր սառը պատերազմի» սկզբնավորման վրա։ Հոդվածում քննարկման առարկա է դարձել տվյալ ժամանակահատվածում Աֆղանստանի նկատմամբ ԱՄՆ քաղաքականության տարբեր դրսևորումները։ Այդ քաղաքականության ձևավորման նախադրյալները, փոփոխությունների պատճառները և զարգացման տրամաբանությունը։
Keywords: Administration’s policy